2008
DOI: 10.1002/jor.20634
|View full text |Cite
|
Sign up to set email alerts
|

Association of KLOTHO gene polymorphisms with knee osteoarthritis in Greek population

Abstract: Based on the fact that klotho-deficient mice exhibit multiple aging phenotypes, including osteopenia and subchondral sclerosis of joints and on the recent observation that KLOTHO gene plays an important role in calcium/phosphate homeostasis, we explored the possibility whether human KLOTHO gene polymorphisms are associated with osteoarthritis (OA). A total of 752 individuals participated in the study. The knee OA group consisted of 369 patients; 298 women (mean age 65.9 AE 8.2; range 40-92 years) and 71 men (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
0
16
0
2
Order By: Relevance
“…This could be an effect of the model as OE mice overexpress only ~1.5x normal KL (Kurosu et al 2005). However, the cognitive enhancing human polymorphism, KL-VS, also arises with mild serum KL elevation (Dubal et al 2014) and minor polymorphic KL changes correlate with human disease risk (Arking et al 2002; Kawano et al 2002; Arking et al 2005; Deary et al 2005; Tsezou et al 2008). As such, mild KL increase or decrease may be sufficient to affect brain function especially with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…This could be an effect of the model as OE mice overexpress only ~1.5x normal KL (Kurosu et al 2005). However, the cognitive enhancing human polymorphism, KL-VS, also arises with mild serum KL elevation (Dubal et al 2014) and minor polymorphic KL changes correlate with human disease risk (Arking et al 2002; Kawano et al 2002; Arking et al 2005; Deary et al 2005; Tsezou et al 2008). As such, mild KL increase or decrease may be sufficient to affect brain function especially with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in allele frequencies of G-395A and those of the C1818T between HD patients and healthy subjects. Kawano et al[ 10] reported that the allele frequency for the A allele in G-395A was 0.128 and for the T allele in C1818T it was 0.248 in Japanese healthy women over 65 years. Our results on allele frequency are almost consistent with the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…A map of KLOTHO is shown in figure 1. One SNP located in the promoter region (G-395A) has been reported to be associated with bone mineral density [8, 9], osteoarthritis [10], systolic blood pressure [11], atherosclerotic coronary artery disease [12, 13], and cardioembolic stroke [14]. Another SNP located in exon 4 (C1818T) has been reported to be associated with bone mineral density [8], fasting glucose [11], and atherosclerotic coronary artery disease [13].…”
Section: Introductionmentioning
confidence: 99%
“…, 2014). The KL-VS variant spans exon 2 and its flanking sequence, and is common in Caucasians (Low et al , 2005; Freathy et al , 2006; Riancho et al , 2007; Novelli et al , 2008; Tsezou et al , 2008; Invidia et al , 2010; Nzietchueng et al , 2011; Tavakkoly-Bazzaz et al , 2011). KL-VS can influence KLOTHO gene expression in vitro, and it has been inconsistently associated with human longevity in European and American populations (Majumdar et al, 2010).…”
mentioning
confidence: 99%